Direct-acting antivirals (DAA) positively affect depression and cognitive function in patients with chronic hepatitis C - Tomasz Pawłowski; Marek Radkowski; Karol Perlejewski; Bogna Szymańska; Hanna Berak; Andrzej Horban; Tomasz Laskus (PLoS ONE, 2025)
The aim of the study was to determine how depression and cognitive dysfunction in patients with chronic hepatitis C virus (HCV) infection are affected by treatment with direct-acting antivirals (DAA). Fifty-two chronic hepatitis C patients underwent neurocognitive and psychological evaluation before therapy and 5–6 months later. Depression was measured by Beck Depression Inventory (BDI), anxiety by State-Trait Anxiety inventory (STAI), neuroticism by Eysenck Personality Inventory (N/EPO-R), while Ruff Figural Fluency Test (RFFT), Wisconsin Card Sorting Test (WCST), The Grooved Pegboard Test (GPT), and California Verbal Learning Test (CVLT) were used to assess neurocognitive function. There was significant positive change in BDI scores (8.8 ± 6.6 vs 6.1 ± 6.1; p < 0.0001) while the most striking improvement in cognitive tests was observed for CVLT sum of immediate recall from Trial-1 to Trial-5 (50.9 ± 10.0 to 54.1 ± 10.0; p = 0.0005) and RFFT, where the number of unique designs increased from 77.2 ± 21.0 to 86.1 ± 28.3 (p < 0.0001). These differences remained significant when patients with advanced (METAVIR grade F3/F4) and those with mild (grade F0/F1/F2) liver disease were analyzed separately, although in general the improvements were more pronounced in the former group. In conclusion, in chronic HCV infection the brain function is markedly improved by DAA treatment.